Sintesis Lapisan Tipis Komposit Ni-TiAlN Menggunakan Teknik Elektrodeposisi pada Berbagai Substrat - Muarief Muarief; Esmar Budi; Iwan Sugihartono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Composite coating on metal is subjected to improve its wear and corrosion resistances. Electrodeposited Ni-TiAlN composite film using variations of metal or metal alloy type as substrate has been investigated. Variation of substrate type used amount 3 variations that are High Speed Steel (HSS), Brass and Galvanis. On this experiment, the electrolyte composition consist of 0.38 M Ni2SO4.6H2O, 0.17 M NiCl2.6H2O and 0.49 M H3BO3 added with each 6 gr/liter amounts of TiN and AlN powders and Dodecyl Sulfate Sodium (C12H25NaO4S) 0.5 gr/liter as sufraktan. The experiment was performed at electrodeposition current of 3.0 mA for about 15 minutes. The results show that the composite film morphology is different in each substrate.Keywords: Elektrodeposition, Ni-TiAlN composite film, High Speed Steel, Brass, Galvanis.